(untitled) (Proceeding of the International Conference on Arts and Humanities, 2020)
This paper aims to explore more issues informing contemporary graphic design education to produce qualified graphic designers ready for the job market. The paper examines the role of talent and skill, with the purpose to answer the question of which one is more critical when producing visual communication materials. To answer this question, the author conducted and supervised several experiments on design students and fresh graduates over a period of two years. The students were exposed to different assignments in which some of these assignments were to produce designs for actual clients, budget, and deadlines. A sample of an assignment would include design and produce a multipage publication, short movie, and poster design. All participants in this study were unfamiliar with the proper techniques and programs, besides the equipment needed to produce their assignments. They were asked to attend briefings and follow-up meetings with the clients. They have been treated as full-time employees; they worked eight hours a day and were given tight deadlines to deliver. The study found that both talent and skill are essential concerning practicing visual communication design. It also revealed that talent ranks before skill.